Commentary on the Apocalypse - Andreas Caesariensis -637 (The fathers of the church, 2011)
In 611 Andrew of Caesarea applied his superior exegetical skills to the challenging Book of Revelation and concluded that the end was not near, in spite of the crises that the empire was facing